Hipotireoidismo e sua associação com depressão em idosos - Borges, Daniela Teixeira (2012)
Objective: To identify the prevalence of hypothyroidism in the elderly attended by the Family Health Strategy (FHS) of Santa Cruz do Sul/RS. Verify what is your association and correlation with depression in the elderly and socio-demographic factors and comorbidities are associated with these diseases. Methods: transversal study with 57 elderly who live in the area registered in the FHS in Santa Cruz do Sul/RS. Data were collected through a structural questionnaire, Mini-Mental and Geriatric Depression Scale GDS-15. Results: 49.1% are male, mean age of 67.7 years, 61.4% married, median years of education 4 years, 89.5% with weekly family living, only 6% live alone, number of child 3.52 (DP: 2.22); median living in the same address 30 years (DP: 15.31); 93% use exclusively SUS; 82.5% use medicines continuously; TSH average of 2.81; minimum and maximum values of F-T4 of 0.89 and 9.88 respectively. The results showed that the prevalence of hypothyroidisms in the in the elderly in the studied was of 17,5%, all of these are subclinical; the depression prevalence was 28,1%, from which 26,3% were diagnosed with mild to moderate depression, and 1,8% with severe depression. Discussion and Conclusions: These elderly need of integral and multidisciplinary interventions aiming at the reduction of the associated factors and at the qualification of their lives.